Investigating Talent Management and Intention to Stay as Mediating Transformational Leadership on Employee Performance - Saptoprasetyo, Yulianto; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Syntax Corporation, 2024)
A great leadership is imperative for organization wanted to achieve their goals. Transformational leaders will transform and to realize performance outcomes who is able to motivate, inspires and create a commitment with their followers. This study’s aims to have better understanding the influence of transformational leadership on employee performance, by investigating the mediating role of talent management and intention to stay. The research uses SPSS.25 to correlate between each indicator score with the total construct score to determine. To test the hypothesis and cause and effect depiction’s using AMOS software using Structure Equation Model (SEM) to see both, the direct and undirect correlation between indicators. The sample was 200 public servant working in government agencies located in Jakarta using online surveys with non-contrived setting in cross sectional survey design. The results indicate transformational leadership has a significant positive influence on employee performance as talent management and intention to stay as a mediator. Government agencies are improving their human capital management strategies, as they realize that it leads to increase in productivity, innovation, improved rates of participation which all contribute to society welfare and economy. This study should be able to stress the importance factors of transformational leadership in implementation of talent management, and how intention to stay effects performance of the employee. Transformational leadership has been around over decades, but there is remains a lack of comprehensive studies regarding the influence of talent management and intention to stay and provide different perspective for governments in implementing talent management strategies.